Social Interaction and Religious Tolerance in Education: A Case Study of Islamic and Buddhist Communities in Gondang Village, North Lombok - Deliyati, April; Maemunah, Maemunah; Isnaini, Isnaini (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KH. EZ. Muttaqien Purwakarta, 2025)
This study aims to analyze social interaction and interfaith tolerance in Gondang Village, North Lombok, as well as to explore the factors that support social harmony amidst religious diversity. The background of this research highlights the importance of interfaith tolerance as a fundamental aspect of maintaining peaceful community life. This study employs a qualitative descriptive approach, utilizing data collection techniques such as observation, interviews, and documentation. The subjects of this research include one community leader, three religious leaders, and two government officials. The focus of the study is to observe actions and social reactions that reflect interfaith interaction and to explore tolerance practices implemented by the local community. The findings reveal that religious differences in Gondang Village do not hinder the creation of harmonious relationships. Mutual respect and appreciation are demonstrated through collaboration in social and religious activities, contributing to a safe and peaceful living environment. It can be concluded that harmonious social interaction and tolerance in Gondang Village play a significant role in fostering an inclusive and prosperous community life. This study contributes to the development of interfaith tolerance studies and is relevant for application in multicultural education.